Use of digital media for the education of health professionals in the treatment of childhood asthma - Helena F. Velasco; Catiane Z. Cabral; Paula P. Pinheiro; Rita de Cassia S. Azambuja; Luciano S. Vitola; Márcia Rosa da Costa; Sérgio L. Amantéa (Elsevier, 2015)
Objectives: Inhalation therapy is the main treatment for asthma and its adequate use has been a factor responsible for disease control; therefore, the aim of the study was to determine whether a digital media tool, which features portability on mobile phones, modifies the assimilation of the inhalation technique. Methods: A total of 66 professionals working in the health care area with the pediatric population were selected. They were submitted to a pre-test on their knowledge of inhalation therapy. The professionals were randomized into two groups (A and B). Group A received a media application on their mobile phones showing the steps of inhalation therapy, while group B received the same information in written form only. A post-test was applied after 15 days. The results (pre- and post-) were analyzed by two pediatric pulmonologists. Results: Of the 66 professionals, 87.9% were females. Of a total possible score of ten, the mean score obtained in the pre-test was 5.3 ± 3, and in the second test, 7.5 ± 2 (p < 0.000). There were no significant differences when comparing the two groups (p = 0.726). The nurses had the lowest mean scores in the initial test (2.3 ± 2); however, they were the group that learned the most with the intervention, showing similar means to those of other groups in the second test (6.1 ± 3). Conclusion: There was significant improvement in knowledge about inhalation therapy in all professional categories using both methods, demonstrating that education, when available to professionals, positively modifies medical practice. Resumo: Objetivos: A Inaloterapia representa a principal forma de tratamento da asma e seu uso adequado tem sido fator responsável pelo controle da doença, desse modo o objetivo do estudo foi determinar se uma ferramenta de mídia digital, dotada de portabilidade na forma de telefonia móvel, modifica a assimilação da técnica inalatória. Métodos: Foram selecionados 66 profissionais que atuam na área da saúde com população pediátrica. Estes foram submetidos a um pré-teste sobre seus conhecimentos de inaloterapia. Os profissionais foram randomizados em dois grupos (A e B). Grupo A recebeu em seu telefone móvel um aplicativo de mídia com os passos da inaloterapia, enquanto grupo B recebeu as mesmas informações apenas de forma escrita. Após 15 dias, realizou-se um pós-teste. Os resultados (pré e pós) foram analisados por dois pneumologistas pediátricos. Resultados: Dos 66 profissionais, 87,9% eram do sexo feminino. Num escore total possível de dez, a média das notas obtidas no pré-teste foi de 5,3 ± 3 e as do segundo teste7,5 ± 2 (p < 000). Não houve diferenças significativas comparando os dois grupos (p = 0,726). Os profissionais de enfermagem apresentaram a menor média nas provas iniciais (2,3 ± 2), porém, foi o grupo que aprendeu mais com a intervenção, apresentando média similar aos outros grupos na segunda prova (6,1 ± 3). Conclusão: Houve melhora significativa no conhecimento sobre inaloterapia em todas as categorias profissionais usando ambos os métodos, comprovando que a educação quando disponibilizada aos profissionais, modifica positivamente a prática médica. Keywords: Asthma, Bronchodilators, Prevention & control, Palavras-chave: Asma, Broncodiltadores, Prevenção & Controle